ZrB2-MoSi2 ceramics: A comprehensive overview of microstructure and properties relationships. Part II: Mechanical properties. Issue 6 (June 2019) - Grohsmeyer, Ryan J.; Silvestroni, Laura; Hilmas, Gregory E.; Monteverde, Fredêric; Fahrenholtz, William G.; D'Angió, Andrea; Sciti, Diletta
Abstract: The mechanical behavior of ZrB2 -MoSi2 ceramics made of ZrB2 powder with three different particle sizes and MoSi2 additions from 5 to 70 vol% was characterized up to 1500 °C. Microhardness (12–17 GPa), Young's modulus (450–540 GPa) and shear modulus (190–240 GPa) decreased with both increasing MoSi2 content and with decreasing ZrB2 grain size. Room temperature fracture toughness was unaffected by grain size or silicide content, whilst at 1500 °C in air it increased with MoSi2 and ZrB2 grain size, from 4.1 to 8.7 MPa m ½ . Room temperature strength did not trend with MoSi2 content, but increased with decreasing ZrB2 grain size from 440 to 590 MPa for the largest starting particle size to 700–800 MPa for the finest due to the decreasing size of surface grain pullout. At 1500 °C, flexure strength for ZrB2 with MoSi2 contents above 25 vol% were roughly constant, 400–450 MPa, whilst for lower content strength was controlled by oxidation damages. Strength for compositions made using fine and medium ZrB2 powders increased with increasing MoSi2 content, 250–450 MPa. Ceramics made with coarse ZrB2 displayed the highest strengths, which decreased with increasing MoSi2 content from 600 to 450 MPa.